Societal secrecy and IPO underpricing - Chen, Yangyang; Chui, Andy C.W.; Goyal, Abhinav; Veeraraghavan, Madhu (Journal of Corporate Finance, 2022)
We examine how societal secrecy affects the underpricing of initial public offerings (IPOs). Using a large sample of 18,304 IPOs across 38 countries, we find robust evidence that IPO underpricing is positively related to societal secrecy. Additional analyses reveal that investor protection, market openness, and third-party certification moderate the effect of societal secrecy on IPO underpricing. We find that societal secrecy influences IPO underpricing through the information asymmetry, demand for control, and information cascade channels. Collectively, we show that societal secrecy exerts a strong influence on IPO underpricing globally.